Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

So I found this geek clock and I think that it's pretty cool.

Geeky clock

I'm just wondering if it is possible to achieve the same but with another number.

So here is the problem:

We want to find a number $n \in \mathbb{Z}$ that will be used exactly $k \in \mathbb{N}^+$ times in any mathematical expresion to produce results in range $[1, 12]$. No rounding, is allowed, but anything fancy it's ok.

If you're answering with an example then use one pair per answer.

I just want to see that clock with another pair of numbers :)

Notes for the current clock:

1 o'clock: using 9 only twice, but it's easy to use it 3 times with many different ways. See comments.

5 o'clock: should be $\sqrt{9}! - \frac{9}{9} = 5$

share|improve this question
7  
They should have multiplied $\dfrac 99$ with $0.\overline 9$. –  Phira Jun 2 '12 at 13:43
2  
Or write $\dfrac{\sqrt{9}\sqrt{9}}{9}$ –  Américo Tavares Jun 2 '12 at 13:43
3  
@Lipis This is not very hard. If you just want to make some small examples, I would recommend doing it by hand. Anyway, I just noticed that the clock is wrong at 5. –  Phira Jun 2 '12 at 13:46
3  
@Phira It's not wrong at 5 if you see it like: (sqrt(9))! - 9/9 = 5 –  Lipis Jun 2 '12 at 13:47
4  
@Lipis but it does say $\sqrt{9!}-\frac{9}{9}$. –  user20266 Jun 2 '12 at 13:52

14 Answers 14

up vote 13 down vote accepted

For $n=12$ and $k=12$ here is a solution:

$1=\frac{12}{12+12+12+12+12+12-(12+12+12+12+12)}$

$2=\left(12 \times \frac{12}{12-12+12-12+12+12+12+12+12+12}\right)$

$3=\left(12 \times \frac{12}{\left(12-\left(12+\left(12+\left(12-\left(12+\left(12+\left(12+\left(12+\left(12+12\right)\right)\right)\right)\right)\right)\right)\right)\right)}\right)$

$4=\left(12-\frac{12}{\left(12 \times \frac{12}{\left(12+\left(12+\left(12+\left(12+\left(12+\left(12+\left(12+12\right)\right)\right)\right)\right)\right)\right)}\right)}\right)$

$5=\left(12 \times \frac{12}{\left(12 \times \left(12 \times \frac{12}{\left(12-\left(12-\left(12+\left(12+\left(12+\left(12+12\right)\right)\right)\right)\right)\right)}\right)\right)}\right)$

$6=\left(12+\frac{12}{\left(12 \times \frac{12}{\left(12-\left(12+\left(12+\left(12+\left(12+\left(12+\left(12+12\right)\right)\right)\right)\right)\right)\right)}\right)}\right)$

$7=\frac{12}{\left(12 \times \frac{12}{\left(12-\left(12-\left(12+\left(12+\left(12+\left(12+\left(12+\left(12+12\right)\right)\right)\right)\right)\right)\right)\right)}\right)}$

$8=\left(12+\left(12 \times \frac{12}{\left(12+\left(12+\left(12-\left(12+\left(12+\left(12+\left(12+\left(12+12\right)\right)\right)\right)\right)\right)\right)\right)}\right)\right)$

$9=\frac{12}{\left(12 \times \frac{12}{\left(12+\left(12+\left(12+\left(12+\left(12+\left(12+\left(12+\left(12+12\right)\right)\right)\right)\right)\right)\right)\right)}\right)}$

$10=\left(12 \times \frac{12}{\left(12-\left(12 \times \frac{12}{\left(12-\left(12+\left(12+\left(12+\left(12+\left(12+12\right)\right)\right)\right)\right)\right)}\right)\right)}\right)$

$11=\left(12+\frac{12}{\left(12-\left(12 \times \left(12 \times \frac{12}{\left(12+\left(12+\left(12+\left(12+\left(12+12\right)\right)\right)\right)\right)}\right)\right)\right)}\right)$

$12=\left(12+\left(12+\left(12-\left(12 \times \left(12 \times \frac{12}{\left(12+\left(12+\left(12+\left(12+\left(12+12\right)\right)\right)\right)\right)}\right)\right)\right)\right)\right)$

share|improve this answer
2  
guys, help me validate this –  tzador Jun 2 '12 at 16:41
18  
While this is impressive I'm not sure how'd it would go on a clock. –  Eugene Jun 2 '12 at 17:12

Seems like $2$ would do it:

$$ 1: 2^2 - 2 - 2/2 $$

$$ 2:2^2 - 2^2 + 2 $$

$$ 3: 2 + 22/22 $$

$$ 4: 2^{2^2}/2^2 $$

$$ 5: 2^2 - 2/2 + 2 $$

$$ 6: 2^2 + 2 - 2 + 2 $$

$$ 7:2^2 + 2 + 2/2 $$

$$ 8:2^{2}(2) + 2 - 2 $$

$$ 9:2^2(2) + 2/2 $$

$$ 10:22/2 - 2/2 $$

$$ 11 : (2^2)!/2 - 2/2 $$

$$ 12: 2^{2^2} - 2^2 $$

That should do it. Thanks to Phira for $10$ and $11$ and Peter for $3$.

share|improve this answer
1  
$(2*2)!/2-2/2$ if you prefer –  Phira Jun 2 '12 at 14:28
1  
And $10=22/2-2/2$ –  Phira Jun 2 '12 at 14:29
2  
Your 3. has only four 2s. $2 + 22/22$ would do. –  Peter Phipps Jun 2 '12 at 14:39
2  
Are you saying that $1=2-2/2+2/2=2-1+1=2$? Does that mean that I don't have to write my thesis because you found a contradiction in mathematics? Awesome. –  Asaf Karagila Jun 2 '12 at 17:36
2  
I don't like those 22. $3 = \frac{(2+2)!}{(2*2*2)}$ $10 = \frac{(2^{2+2})}{2} +2$ –  Fabio F. Jun 2 '12 at 20:14

Making numbers out of 4 fours is a common problem: $$1=\frac {44}{44}$$ $$2=\frac {4\cdot 4}{4+4}$$ $$3=\frac{4+4+4}{4}$$ $$4=\frac{4-4}{4}+4$$ $$5=\sqrt{4!+\frac{\sqrt 4+\sqrt 4} 4}$$ $$6=\sqrt{\frac{4!\cdot 4-4!}{\sqrt 4}}$$ $$7=\sqrt{4!\sqrt 4+\frac 4 4}$$ $$8=\sqrt{\frac{4^4}{\sqrt4+\sqrt 4}}$$ $$9=(4-\frac 4 4)^{\sqrt 4}$$ $$10=\frac{4!} 4 - (4-\sqrt 4)$$ $$11=\frac{4!}{\sqrt 4}-\frac 4 4$$ $$12=\sqrt{\frac{4!4!}{\sqrt 4+\sqrt 4}}$$

You should clarify what operations you want. If you allow for any kind of rounding function, factorials and logs you can almost certainly do it with one of any number (though the resulting expressions may not fit on a clock).

share|improve this answer
    
I think the problem with square roots is that they're implicitly using twos. –  Eugene Jun 2 '12 at 14:57
    
Without rounding as long as it's valid. –  Lipis Jun 2 '12 at 15:00
    
@Eugene the $\sqrt 9$s in the clock are then implicitly $3$s, and the $4!$ is implicitly 24, no? I'm not really arguing; I can try an minimize my use of them but I assumed they were allowed given that they appeared in the original clock. –  Robert Mastragostino Jun 2 '12 at 15:05
    
I think given the original parameters of the question it's valid. I was just thinking that square roots use twos implicitly. Wasn't trying to deride your fine answer. Sorry if it came off that way. –  Eugene Jun 2 '12 at 15:06
1  
point taken. :) –  Robert Mastragostino Jun 2 '12 at 20:00

Now with $n = 5$ and $k = 5$.

With $n = 5$ and $k = 5$ (missing a $9$ for now but I'll come back to it later).

$\dfrac{55}{5}-5-5=1$

$\dfrac{5+5}{5}-5+5=2$

$\dfrac{5+5}{5}+\frac{5}{5}=3$

$\dfrac{5+5+5+5}{5}=4$

$5 - 5 + 5 - 5 + 5 = 5$

$5 + \dfrac{5}{5} - 5 + 5 = 6$

$5 + \dfrac{5}{5}+\dfrac{5}{5} = 7$

$5 + 5 - \dfrac{5+5}{5} = 8$

$5 + \dfrac{5(5) - 5}{5}=9$

$\dfrac{55}{5} - \dfrac{5}{5} = 10$

$\dfrac{55}{5} - 5 + 5 = 11$

$\dfrac{5+5}{5} + 5 + 5 = 12$

Thanks to tzador for $9$.

share|improve this answer
3  
$\left(5+\frac{5!}{\left(5+\left(5 \times 5\right)\right)}\right)=9$ –  tzador Jun 2 '12 at 16:03
3  
$9=\left(5-\frac{\left(5-\left(5 \times 5\right)\right)}{5}\right)$ what about this one? –  tzador Jun 2 '12 at 16:46
    
I don't think 55 counts as two instances of five; it's a separate number, after all. –  jwodder Jun 2 '12 at 20:19
1  
You should look at the original clock. –  Eugene Jun 2 '12 at 20:20

For $n=4$ and $k=5$ here is a solution:

$\frac{4}{\left(4+\left(4 \times \left(4-4\right)\right)\right)}=1$

$\left(4-\left(4 \times \frac{4}{\left(4+4\right)}\right)\right)=2$

$\left(4+\frac{4}{\left(4-\left(4+4\right)\right)}\right)=3$

$\left(4+\left(4+\left(4-\left(4+4\right)\right)\right)\right)=4$

$\left(4-\frac{4}{\left(4-\left(4+4\right)\right)}\right)=5$

$\left(4+\left(4 \times \frac{4}{\left(4+4\right)}\right)\right)=6$

$\frac{4}{\left(4 \times \frac{4}{\left(4+4!\right)}\right)}=7$

$\left(4 \times \left(4 \times \frac{4}{\left(4+4\right)}\right)\right)=8$

$\left(4-\left(\frac{4}{4}-\frac{4!}{4}\right)\right)=9$

$\left(4+\frac{4}{\left(4 \times \frac{4}{4!}\right)}\right)=10$

$\frac{4}{\left(4 \times \frac{4}{44}\right)}=11$

$\left(4-\left(4-\left(4+\left(4+4\right)\right)\right)\right)=12$

share|improve this answer

For $n=9$ and $k=9$ here is a solution:

$1=\left(9+\frac{9}{\left(9 \times \frac{9}{\left(9+\left(9+\left(9-99\right)\right)\right)}\right)}\right)$

$2=\frac{9}{\left(9+\frac{9}{\left(9-\frac{9}{\left(9 \times \frac{9}{99}\right)}\right)}\right)}$

$3=\left(9-\left(9+\left(9-\frac{9}{\left(9 \times \frac{9}{\left(9+99\right)}\right)}\right)\right)\right)$

$4=\left(9-\frac{9}{\left(9 \times \frac{9}{\left(9+\left(9+\left(9+\left(9+9\right)\right)\right)\right)}\right)}\right)$

$5=\left(9+\left(9-\frac{9}{\left(9 \times \frac{9}{\left(9+\left(9+99\right)\right)}\right)}\right)\right)$

$6=\left(9+\frac{9}{\left(9-\frac{9}{\left(9 \times \frac{9}{\left(9+99\right)}\right)}\right)}\right)$

$7=\left(9+\left(9+\frac{9}{\left(9 \times \frac{9}{\left(9-\left(9+99\right)\right)}\right)}\right)\right)$

$8=\left(9+\left(9 \times \frac{9}{\left(9+\left(9+\left(9-\left(9+99\right)\right)\right)\right)}\right)\right)$

$9=\left(9 \times \left(9 \times \frac{9}{\left(9-\left(9+\left(9+\left(9-99\right)\right)\right)\right)}\right)\right)$

$10=\left(9-\left(9 \times \frac{9}{\left(9+\left(9+\left(9-\left(9+99\right)\right)\right)\right)}\right)\right)$

$11=\frac{9}{\left(9 \times \frac{9}{\left(9-\left(9+\left(9-\left(9+99\right)\right)\right)\right)}\right)}$

$12=\left(9-\frac{9}{\left(9-\frac{9}{\left(9 \times \frac{9}{\left(9+99\right)}\right)}\right)}\right)$

share|improve this answer

For $1$ here is a solution:

$$ 1 = 1 $$

$$ 1+1 = 2 $$

$$ 1+1+1 = 3 $$

$$ 1+1+1+1 = 4 $$

$$ 1+1+1+1+1 = 5 $$

$$ 1+1+1+1+1+1 = 6 $$

$$ 1+1+1+1+1+1+1 = 7 $$

$$ 1+1+1+1+1+1+1+1 = 8 $$

$$ 1+1+1+1+1+1+1+1+1 = 9 $$

$$ 1+1+1+1+1+1+1+1+1+1 = 10 $$

$$ 1+1+1+1+1+1+1+1+1+1+1 = 11 $$

$$ 1+1+1+1+1+1+1+1+1+1+1+1 = 12 $$

share|improve this answer
7  
1 = 1, 2 = 2, 3 = 3, 4 = 4, 5 = 5, 6 = 6, 7 = 7, 8 = 8, 9 = 9, 10 = 10, 11 = 11, 12 = 12 –  tzador Jun 2 '12 at 16:55
1  
We are to fix n and k... –  The Chaz 2.0 Jun 2 '12 at 17:48
    
I don't understand the downvotes. It's trivial to fix, e.g. $8=1\cdot 1\cdot1\cdot1(1+1+1+1+1+1+1+1)$, $n=1$ & $k=12$. –  Jonas Meyer Jun 2 '12 at 22:58
1  
@JonasMeyer: Except that was my answer –  Eric Jun 2 '12 at 23:02
1  
Oh, apparently someone else posted that as a new answer. instead. (Edit) @Eric: Yes, I see that now. It wasn't your answer until 9 minutes ago, and I hadn't seen it. –  Jonas Meyer Jun 2 '12 at 23:02

For $n=19$ and $k=19$ here is a solution:

$1=\frac{19}{\left(19+\left(19 \times \left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19-\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+19\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)}$

$2=\frac{19}{\left(19 \times \frac{19}{\left(19-\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19-\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+19\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)}\right)}$

$3=\left(19-\left(19+\frac{19}{\left(19-\left(19 \times \frac{19}{\left(19+\left(19 \times \frac{19}{\left(19+\left(19+\left(19-\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+19\right)\right)\right)\right)\right)\right)\right)\right)\right)}\right)\right)}\right)\right)}\right)\right)$

$4=\left(19-\frac{19}{\left(19 \times \frac{19}{\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+19\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)}\right)}\right)$

$5=\left(19 \times \frac{19}{\left(19+\left(19+\left(19+\left(19+\left(19 \times \frac{19}{\left(19+\left(19+\left(19-\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+19\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)}\right)\right)\right)\right)\right)}\right)$

$6=\left(19+\left(19-\left(19+\frac{19}{\left(19 \times \frac{19}{\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+19\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)}\right)}\right)\right)\right)$

$7=\left(19-\left(19 \times \frac{19}{\left(19-\left(19 \times \frac{19}{\left(19+\left(19 \times \left(19 \times \frac{19}{\left(19-\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+19\right)\right)\right)\right)\right)\right)\right)\right)}\right)\right)\right)}\right)\right)}\right)\right)$

$8=\left(19+\frac{19}{\left(19 \times \frac{19}{\left(19+\left(19-\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+19\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)}\right)}\right)$

$9=\left(19 \times \frac{19}{\left(19+\left(19-\left(19 \times \frac{19}{\left(19+\left(19-\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+19\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)}\right)\right)\right)}\right)$

$10=\frac{19}{\left(19 \times \frac{19}{\left(19-\left(19+\left(19+\left(19-\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+19\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)}\right)}$

$11=\left(19+\frac{19}{\left(19-\left(19 \times \frac{19}{\left(19+\left(19 \times \frac{19}{\left(19-\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+19\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)}\right)\right)}\right)\right)}\right)$

$12=\frac{19}{\left(19 \times \frac{19}{\left(19-\left(19+\left(19-\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+\left(19+19\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)}\right)}$

share|improve this answer
3  
One wonders how this would go on a clock. –  Eugene Jun 2 '12 at 18:32
2  
@Eugene: Not only one, even two, three and four ... –  Gigili Jun 2 '12 at 18:52

solution for n = 1, k = 12:

$$ 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1 = 1 $$

$$ 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1+1 = 2 $$

$$ 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1+1+1 = 3 $$

$$ 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1+1+1+1 = 4 $$

$$ 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1+1+1+1+1 = 5 $$

$$ 1 \times 1 \times 1 \times 1 \times 1 \times 1 \times 1+1+1+1+1+1 = 6 $$

$$ 1 \times 1 \times 1 \times 1 \times 1 \times 1+1+1+1+1+1+1 = 7 $$

$$ 1 \times 1 \times 1 \times 1 \times 1+1+1+1+1+1+1+1 = 8 $$

$$ 1 \times 1 \times 1 \times 1+1+1+1+1+1+1+1+1 = 9 $$

$$ 1 \times 1 \times 1+1+1+1+1+1+1+1+1+1 = 10 $$

$$ 1 \times 1+1+1+1+1+1+1+1+1+1+1 = 11 $$

$$ 1+1+1+1+1+1+1+1+1+1+1+1 = 12 $$

share|improve this answer
    
This is one way to adjust Evan Carroll's answer to better fit the question's specifications. –  Jonas Meyer Jun 2 '12 at 23:10
1  
This also has the nice property of having lines of identical length –  Eric Jun 2 '12 at 23:12

For $n=2$ and $k=12$ here is a solution:

$1=\left(2 \times \left(2 \times \left(2 \times \frac{2}{\left(2+\left(2+\left(2+\left(2+\left(2+\left(2+\left(2+2\right)\right)\right)\right)\right)\right)\right)}\right)\right)\right)$

$2=\left(2+\left(2 \times \left(2+\left(2+\left(2+\left(2+\left(2-\left(2+\left(2+\left(2+\left(2+2\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)$

$3=\left(2 \times \left(2+\left(2 \times \frac{2}{\left(2+\left(2-\left(2+\left(2+\left(2+\left(2+\left(2+2\right)\right)\right)\right)\right)\right)\right)}\right)\right)\right)$

$4=\frac{2}{\left(2 \times \left(2 \times \frac{2}{\left(2+\left(2+\left(2+\left(2+\left(2+\left(2+\left(2+2\right)\right)\right)\right)\right)\right)\right)}\right)\right)}$

$5=\frac{2}{\left(2 \times \frac{2}{\left(2-\left(2+\left(2-\left(2+\left(2+\left(2+\left(2+\left(2+2\right)\right)\right)\right)\right)\right)\right)\right)}\right)}$

$6=\left(2-\frac{2}{\left(2 \times \frac{2}{\left(2+\left(2-\left(2+\left(2+\left(2+\left(2+\left(2+2\right)\right)\right)\right)\right)\right)\right)}\right)}\right)$

$7=\frac{2}{\left(2 \times \frac{2}{\left(2-\left(2-\left(2+\left(2+\left(2+\left(2+\left(2+\left(2+2\right)\right)\right)\right)\right)\right)\right)\right)}\right)}$

$8=\left(2-\left(2+\left(2+\left(2+\left(2-\left(2+\left(2+\left(2+\left(2+\left(2+\left(2+2\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)$

$9=\frac{2}{\left(2 \times \frac{2}{\left(2+\left(2+\left(2+\left(2+\left(2+\left(2+\left(2+\left(2+2\right)\right)\right)\right)\right)\right)\right)\right)}\right)}$

$10=\left(2+\frac{2}{\left(2 \times \frac{2}{\left(2+\left(2+\left(2+\left(2+\left(2+\left(2+\left(2+2\right)\right)\right)\right)\right)\right)\right)}\right)}\right)$

$11=\left(2+\left(2+\frac{2}{\left(2 \times \frac{2}{\left(2+\left(2+\left(2+\left(2+\left(2+\left(2+2\right)\right)\right)\right)\right)\right)}\right)}\right)\right)$

$12=\left(2-\left(2+\left(2+\left(2-\left(2+\left(2+\left(2+\left(2+\left(2+\left(2+\left(2+2\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)$

share|improve this answer
    
actuall for k in [1..12] and n = 12 there is a solutions –  tzador Jun 2 '12 at 23:03

Six ones. For ease of reading, I write $n$ for the sum of $n$ 1s, so for example I mean

$1 = ((1+1+1)-(1+1)) \times 1$.

Here are the expressions:

$1 = (3-2) \times 1$

$2 = 4-2$

$3 = (4-1) \times 1$

$4 = 5-1$

$5 = 5 \times 1$

$6 = 6$

$7 = (3 \times 2) + 1$

$8 = 4 \times 2$

$9 = 3 \times 3$

$10 = (3! - 1) \times 2$

$11 = (3! \times 2) - 1$

$12 = 3! \times 2 \times 1$

Any larger number of 1s is possible (just multiply these expressions by 1 as many times as necessary); I don't think five ones is possible.

share|improve this answer
    
What's your n and k? –  Lipis Jun 2 '12 at 23:03
    
"I don't think five ones is possible."--That is interesting. What restrictions do you have in mind for what operations/functions are allowed? –  Jonas Meyer Jun 2 '12 at 23:07
    
$n = 1, k = 6$; I had in mind addition, subtraction, multiplication, division, exponentiation, square roots, and factorials. (To be honest I didn't try that hard to get down to $k = 5$.) –  Michael Lugo Jun 2 '12 at 23:09
    
@JonasMeyer Any number as long as the expression uses only that number as is. For n=14 the number a=141414 also allowed.. –  Lipis Jun 2 '12 at 23:10
1  
If we allow $11$ (using two 1s) then $n = 1$, $k = 5$ is possible. I suppose allowing concatenation is implicit in the way the original clock is set up. –  Michael Lugo Jun 2 '12 at 23:12

For $n=-1$ and $k=8$ here is a solution:

$1=\left(-1-\left(-1 \times \left(-1+\left(-1-\left(-1+\left(-1+\left(-1+-1\right)\right)\right)\right)\right)\right)\right)$

$2=\left(-1+\left(-1+\left(-1-\left(-1+\left(-1+\left(-1+\left(-1+-1\right)\right)\right)\right)\right)\right)\right)$

$3=\left(-1-\left(-1 \times \left(-1-\left(-1+\left(-1+\left(-1+\left(-1+-1\right)\right)\right)\right)\right)\right)\right)$

$4=\left(-1+\left(-1-\left(-1+\left(-1+\left(-1+\left(-1+\left(-1+-1\right)\right)\right)\right)\right)\right)\right)$

$5=\left(-1+\left(-1 \times \left(-1+\left(-1+\left(-1+\left(-1+\left(-1+-1\right)\right)\right)\right)\right)\right)\right)$

$6=\left(-1-\left(-1+\left(-1+\left(-1+\left(-1+\left(-1+\left(-1+-1\right)\right)\right)\right)\right)\right)\right)$

$7=\left(-1 \times \left(-1+\left(-1+\left(-1+\left(-1+\left(-1+\left(-1+-1\right)\right)\right)\right)\right)\right)\right)$

$8=\left(-1 \times \left(-1+\left(-1-\left(\left(-1+-1\right) \times \left(-1+\left(-1+-1\right)\right)\right)\right)\right)\right)$

$9=\left(-1 \times \left(-1-\left(\left(-1+-1\right) \times \left(-1+\left(-1+\left(-1+-1\right)\right)\right)\right)\right)\right)$

$10=\left(-1 \times \left(-1-\left(\left(-1+\left(-1+-1\right)\right) \times \left(-1+\left(-1+-1\right)\right)\right)\right)\right)$

$11=\left(-1-\left(\left(-1+-1\right) \times \left(\left(-1+-1\right) \times \left(-1+\left(-1+-1\right)\right)\right)\right)\right)$

$12=\left(-1 \times \left(\left(-1+-1\right) \times \left(\left(-1+-1\right) \times \left(-1+\left(-1+-1\right)\right)\right)\right)\right)$

share|improve this answer
    
I will update my question to include negative numbers as well.. why not? –  Lipis Jun 2 '12 at 23:12

or $n=-12$ and $k=12$ here is a solution:

$1=\frac{-12}{\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+\left(-12-\left(-12+\left(-12+\left(-12+\left(-12+-12\right)\right)\right)\right)\right)\right)\right)\right)\right)\right)}$

$2=\left(-12 \times \frac{-12}{\left(-12+\left(-12-\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+-12\right)\right)\right)\right)\right)\right)\right)\right)\right)}\right)$

$3=\left(-12 \times \frac{-12}{\left(-12+\left(-12+\left(-12-\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+-12\right)\right)\right)\right)\right)\right)\right)\right)\right)}\right)$

$4=\left(-12-\left(-12 \times \frac{-12}{\left(-12+\left(-12 \times \frac{-12}{\left(-12-\left(-12+\left(-12+\left(-12+\left(-12+-12\right)\right)\right)\right)\right)}\right)\right)}\right)\right)$

$5=\left(-12-\left(-12+\frac{-12}{\left(-12 \times \frac{-12}{\left(-12-\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+-12\right)\right)\right)\right)\right)\right)}\right)}\right)\right)$

$6=\left(-12+\left(-12 \times \left(-12 \times \frac{-12}{\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+-12\right)\right)\right)\right)\right)\right)\right)}\right)\right)\right)$

$7=\frac{-12}{\left(-12 \times \frac{-12}{\left(-12-\left(-12-\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+-12\right)\right)\right)\right)\right)\right)\right)\right)}\right)}$

$8=\left(-12-\left(-12+\left(-12+\left(-12 \times \frac{-12}{\left(-12+\left(-12-\left(-12+\left(-12+\left(-12+\left(-12+-12\right)\right)\right)\right)\right)\right)}\right)\right)\right)\right)$

$9=\frac{-12}{\left(-12 \times \frac{-12}{\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+-12\right)\right)\right)\right)\right)\right)\right)\right)}\right)}$

$10=\left(-12 \times \frac{-12}{\left(-12-\left(-12+\left(-12+\left(-12 \times \frac{-12}{\left(-12+\left(-12+\left(-12+\left(-12+-12\right)\right)\right)\right)}\right)\right)\right)\right)}\right)$

$11=\left(-12-\frac{-12}{\left(-12 \times \frac{-12}{\left(-12-\left(-12 \times \left(-12+\left(-12-\left(-12+\left(-12+\left(-12+-12\right)\right)\right)\right)\right)\right)\right)}\right)}\right)$

$12=\left(-12-\left(-12 \times \left(-12 \times \frac{-12}{\left(-12-\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+\left(-12+-12\right)\right)\right)\right)\right)\right)\right)}\right)\right)\right)$

share|improve this answer

For $n=3$ and $k = 3$.

$1 = 3^{3-3}$

$2 = 3-\frac{3}{3}$

$3 = 3+3-3$

$4 = 3+\frac{3}{3}$

$5 = 3!-\frac{3}{3}$

$6 = 3*3-3$

$7 = 3!+\frac{3}{3}$

$8 = \pi(3)*\pi(3)*\pi(3)$

$9 = 3+3+3$

$10 = 3!+\pi(3)+\pi(3)$

$11 = 3!+3+\pi(3)$

$12 = 3*3+3$

share|improve this answer
    
What is $\pi(3)$? It's 2 in your case.. but any reference? –  Lipis Jun 4 '12 at 6:51
2  
It's the prime-counting function. $\pi(x)$ is the number of prime numbers equal or less than x. –  Panu Horsmalahti Jun 4 '12 at 12:15
    
Awesome...! Thanks –  Lipis Jun 4 '12 at 12:54

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.